2006
DOI: 10.1074/jbc.m511560200
|View full text |Cite
|
Sign up to set email alerts
|

6-Hydroxydopamine-induced Apoptosis Is Mediated via Extracellular Auto-oxidation and Caspase 3-dependent Activation of Protein Kinase Cδ

Abstract: 6-Hydroxydopamine is a neurotoxin commonly used to lesion dopaminergic pathways and generate experimental models for Parkinson disease, however, the cellular mechanism of 6-hydroxydopamine-induced neurodegeneration is not well defined. In this study we have explored how 6-hydroxydopamine neurotoxicity is initiated. We have also investigated downstream signaling pathways activated in response to 6-hydroxydopamine, using a neuronal-like, catecholaminergic cell line (PC12 cells) as an in vitro model system. We ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
149
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(163 citation statements)
references
References 69 publications
12
149
1
Order By: Relevance
“…However, controversy still exists concerning the most important mode of PKC activation [3,4,16,18,19,[28][29][30] . Recent research has suggested that PKCδ phosphorylation at the site of Tyr311 could regulate the proteolytic activation and proapoptotic function of PKCδ in dopaminergic neuronal cells [28] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, controversy still exists concerning the most important mode of PKC activation [3,4,16,18,19,[28][29][30] . Recent research has suggested that PKCδ phosphorylation at the site of Tyr311 could regulate the proteolytic activation and proapoptotic function of PKCδ in dopaminergic neuronal cells [28] .…”
Section: Discussionmentioning
confidence: 99%
“…However, some researchers have suggested that phosphorylation at the site of Thr505 in PKCδ might just lead to the allosteric effect, which is one of the prerequisites for PKCδ activation [19] , and the proteolysis of PKCδ by caspase-3 represents the terminal pattern of PKCδ activation. The accumulation of PKCδ catalytic fragment is an important event in cell apoptosis [18] , particularly in H 2 O 2 -or MPP + -induced cytotoxic responses [29,30] . Our studies demonstrate that 6-OHDA could induce PKCδ phosphorylation at the site of Thr505 in PC12 cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…PC-12 cells exposed to 6-OHDA are widely used as an experimental model of PD in vitro (Blum et al 2001;Hanrott et al 2006;Zhang et al 2012). NGF-induced neurite outgrowth from PC-12 rat pheochromocytoma cells provides a well-characterised model of sympathetic neuron differentiation (Greene & Tischler 1982).…”
Section: Discussionmentioning
confidence: 99%
“…6-OHDA has been found to initiate cellular oxidative stress, and widely used to create both cellular and animal models of PD (Blum et al 2001). Previous studies suggested that the reactive oxygen species (ROS) involved were derived from auto-oxidation (Hanrott et al 2006). NADPH oxidase (NOX)-derived ROS were also found to play an essential role in 6-OHDA-induced cell death (Choi et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, injection of 6-OHDA into rat substantia nigra produced the first toxin animal model of PD (236), where neuronal death reflects an apoptotic mechanism (237). 6-OHDA is an active redox-cycling agent (via its derived quinone and semiquinone), and studies on its biochemical mechanism of toxicity in PC12 cells have found catalase attenuation of neurotoxicity, suggesting that the latter is evoked by H 2 O 2 (238). However, factors other than H 2 O 2 also appear to be involved, because catalase did not inhibit the caspase activation contribution to 6-OHDA neurotoxicity (239).…”
Section: Role Of Oxidative Stress In the Pathogenesis Of Pd And Modelmentioning
confidence: 99%